Design and validation of a multimodal low-budget Raman-microscope for liquid and solid phase applications - Will, Stefan; Koch, Hanna; Noack, Kristina (Optical Methods for Inspection, Characterization, and Imaging of Biomaterials II, 2015)
Confocal Raman microscopy is a powerful tool to measure small sample volumes or solids. Since commercial Raman microscopes are expensive and a change of the laser wavelength or the excitation path is hardly possible after the installation, we constructed a multimodal low-budget Raman microscope. Thus, it was possible to significantly increase the flexibility in terms of excitation wavelengths, paths, and planes. Furthermore, the asset costs were reduced by a factor of 1.7. By using commercial as well as home-built objectives to adapt the working distance and the magnification to the system under investigation, the self-constructed Raman microscope offers the possibility to measure big sample volumes, too. The obtained Raman spectra were validated by Raman spectra from a commercial Raman microscope. With a comparable measurement setting it was possible to increase the signal intensities, but with a slightly lower SNR. However, based on the great flexibility of the set-up, e.g., the laser power or the excitation wavelength can be adapted to increase the SNR. Furthermore, measurement times can be decreased. With this low-budget self-constructed Raman microscope high quality Raman microscopy and micro spectroscopy can be performed with a high flexibility to fast adapt the set-up to the sample under investigation which is not offered by commercial microscope
Keywords: Raman microscope; low-budget; confocal; validation; multimodal; application-oriented

Experimentelle und theoretische Untersuchung optisch aktiver Moleküle zur Online-Analyse der Enantiomertrennung mittels Raman-Spektroskopie - Noack, Kristina; Koch, Hanna; Kiefer, Johannes; Kaspereit, Malte; Will, Stefan (ProcessNet-Jahrestagung 2014, 2014)

High-speed, inline measurement of protein activity and inactivation processes by supercontinuum attenuation spectroscopy - Koch, Hanna; Eisen, Kristina; Werblinski, Thomas; Perlitz, Julian; Prihoda, Felix; Lee, Geoffrey; Will, Stefan (Analyst, 2019)

High-speed, inline measurement of protein activity and inactivation processes by supercontinuum attenuation spectroscopy - Koch, Hanna; Eisen, Kristina; Werblinski, Thomas; Perlitz, Julian; Prihoda, Felix; Lee, Geoffrey; Will, Stefan (Analyst, 2019)
Some proteins such as catalase and glutamate dehydrogenase (GDH) are very sensitive to external factors such as irradiation or heat, which may cause inactivation. Since proteins are used in a wide field of applications, the entire activity has to be ensured during the whole process. By default, activity is measured by invasive and offline activity assays. To avoid the need for a time-consuming offline analysis, we developed an optical high-speed measurement technique, which may form the basis for the non-invasive inline control of enzyme processes e.g. in the textile or food industry. The technique is based on attenuation spectroscopy using a supercontinuum laser source in combination with multivariate data analysis, in particular partial least squares regression (PLSR). For verification of the approach, samples treated by various stresses were analyzed in parallel by activity assays and our new method. Applying this technique, we were able to determine the activity in the turbid catalase samples after heat treatment, addition of guanidine-HCl or irradiation with UV light by applying partial least squares regression. Furthermore, we demonstrate that the combination of broadband attenuation spectroscopy and PLSR enables us to determine also the activity of GDH in clear solutions after heat treatment.
CRIS-Team Scopus Importer:2019-11-26

In situ investigation of the protein particle formation process during drying in an acoustic levitator - Perlitz, Julian; Prihoda, Felix; Koch, Hanna; Lee, Geoffrey; Will, Stefan (International Congress on Particle Technology - PARTEC 2019, 2019)

In-situ-Untersuchung der Strukturveränderungen von Enzymen während der Trocknung in einem akustischen Levitator - Perlitz, Julian; Prihoda, Felix; Koch, Hanna; Lee, Geoffrey; Will, Stefan (ProcessNet-Jahrestagung und 33. DECHEMA-Jahrestagung der Biotechnologien 2018, 2018)

Optical investigation of the drying behavior of protein microdroplets - Perlitz, Julian; Koch, Hanna; Prihoda, Felix; Lee, Geoffrey; Will, Stefan (Sensors Day 2017, Cambridge, UK, 20.10.2017., 2017)

Raman Spectrocopy for non-invasive online measuerements of the pH and CO2 concentration in algal cultivations - Koch, Hanna; Noack, Kristina; Stute, Stephanie; Buchholz, Rainer; Will, Stefan (3rd European Congress of Applied Biotechnology (ECAB), 2015)

Raman-Spektroskopie zur Untersuchung von Biomolekülen - Koch, Hanna (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)
Biomoleküle spielen in vielen Bereichen eine wichtige Rolle. Für den Einsatz müssen die Moleküle bestimmte Voraussetzungen wie vollständige Reinheit oder Aktivität erfüllen. In dieser Arbeit werden Enantiomere, Proteine, CO2 und die Rotalge P. purpureum mittels optischer Messtechniken untersucht. Es erfolgt die optische Differenzierung von Enantiomeren aufgrund enantioselektiver Wechselwirkungen zwischen D-D-, L-L- und D-L-Enantiomeren mittels Raman-Spektroskopie. Durch die Kombination von Raman-Spektroskopie und multivariater Datenanalyse erfolgt die Vorhersage des Verhältnisses von D- zu L-Enantiomer. Raman-Spektroskopie und multivariate Datenanalyse eignen sich für die Bestimmung der Veränderungen der Sekundärstrukturelemente von Proteinen. Dies ist vor allem für die Untersuchung neurodegenerativer Krankheiten von Interesse. Veränderungen in der Proteinstruktur gehen auch mit einem Aktivitätsverlust einher. Daher wird in dieser Arbeit eine nicht-invasive Hochgeschwindigkeits-Breitband-Abschwächungsspektroskopie in Kombination mit multivariater Datenanalyse zur Inline-Vorhersage der Proteinaktivität entwickelt. Es finden Untersuchungen zur CO2-Konzentration und deren Einfluss auf den pH-Wert in wässriger Lösung statt, da hier die Prozesskontrolle und -optimierung von Algenkulturen im Vordergrund stehen. Raman-Mikrospektroskopie eignet sich für die Vorhersage der CO2-Konzentration und des pH-Wertes. In dieser Arbeit werden Biomoleküle mittels Raman-Spektroskopie in Kombination mit weiteren optischen Messmethoden und multivariaten Auswertemethoden analysiert. Damit wird gezeigt, dass diese Kombination möglicherweise für eine Prozesskontrolle und -optimierung geeignet ist. Aufgrund der nicht-invasiven und zerstörungsfreien Messtechniken sind Inline-Messungen möglich.
Keywords: Raman-Spektroskopie; Biomoleküle; Enantiomere; Proteine; CO2